Gut microbiota and endometrial cancer: research progress on the pathogenesis and application - Weiqin Zheng; Xiaowen Lin; Huixin Chen; Ziling Yang; Han Zhao; Shibo Li; Tao Song; Yuhui Sun (Annals of Medicine)
As one of the three major malignant tumors in women, the morbidity of endometrial cancer is second only to that of cervical cancer and is increasing yearly. Its etiological mechanism is not clear, and the risk factors are numerous and common and are closely related to obesity, hypertension, diabetes, etc. The gut microbiota has many strains, which play a considerable part in normal digestion and absorption in the human body and the regulation of the immune response. In the last few years, research on the gut microbiota has been unprecedentedly popular, and it has been confirmed that the gut microbiota closely correlates with the occurrence and development of all kinds of benign and malignant diseases. In this article, the effects of the gut microbiota and its metabolites on the occurrence and development of endometrial cancer is reviewed, and its application in the prevention, diagnosis and treatment of endometrial cancer is explored.